2021
DOI: 10.1272/jnms.jnms.2021_88-405
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Tear Osmolarity after Cataract Surgery

Abstract: Background:The purpose of this study was to examine changes in the ocular surface before and after phacoemulsification with small incisions and to examine the changes in tear osmolarity.Methods: This was a prospective, observational study involving 55 eyes of 39 patients (19 male, 20 female patients; average age 72.0±7.3 years) who had cataract surgery at a Nippon Medical School Hospital between December 2013 and June 2018. Compromised tear dynamics were determined by the Schirmer test or the tear break-up tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…The negative impact of dry eye on the surgical outcome of cataracts has been widely described [ 80 , 81 , 82 , 83 ]. Several studies have shown an increase in the signs and symptoms of dry eye after cataract surgery [ 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. A recent meta-analysis found that patients with prior MGD are at increased risk of postoperative dry eye [ 87 ].…”
Section: Use Of Thermography In Ophthalmologymentioning
confidence: 99%
“…The negative impact of dry eye on the surgical outcome of cataracts has been widely described [ 80 , 81 , 82 , 83 ]. Several studies have shown an increase in the signs and symptoms of dry eye after cataract surgery [ 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. A recent meta-analysis found that patients with prior MGD are at increased risk of postoperative dry eye [ 87 ].…”
Section: Use Of Thermography In Ophthalmologymentioning
confidence: 99%
“…After cataract surgery, signs of dry eye include a decreased tear breakup time, decreased corneal sensitivity, and increased ocular surface staining [ 2 , 4 , 5 ]. The pathogenic factors consist of inflammation, microscopic damage, neurosensory destruction on the ocular surface, tear film instability, and hyperosmolarity [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Đối chiếu độ thẩm thấu nước mắt ở các thời điểm trước mổ, sau mổ 01 tuần, 01 tháng và 03 tháng với các nghiên cứu khác Độ thẩm thấu của phim nước mắt tại thời điểm trước phẫu thuật trong nghiên cứu của chúng tôi cao hơn so với nghiên cứu của Tsutomu Igarashi[10] là do chúng tôi sử dụng máy đo độ thẩm thấu Ipen khác với máy đo độ thẩm thấu TearLab được sử dụng trong nghiên cứu của Tsutomu Igarashi.…”
unclassified